Production and Application of CAR T Cells: Current and Future Role of Europe - Vucinic, Vladan; Quaiser, Andrea; Lückemeier, Philipp; Fricke, Stephan; Platzbecker, Uwe; Koehl, Ulrike (Frontiers in Medicine, 2021)
Rapid developments in the field of CAR T cells offer important new opportunities while at the same time increasing numbers of patients pose major challenges. This review is summarizing on the one hand the state of the art in CAR T cell trials with a unique perspective on the role that Europe is playing. On the other hand, an overview of reproducible processing techniques is presented, from manual or semi-automated up to fully automated manufacturing of clinical-grade CAR T cells. Besides regulatory requirements, an outlook is given in the direction of digitally controlled automated manufacturing in order to lower cost and complexity and to address CAR T cell products for a greater number of patients and a variety of malignant diseases.